Estimation of shale pore-size-distribution from N2 adsorption characteristics employing modified BJH algorithm - He, Yanqing; Chen, Qing; Tian, Yuanyuan; Yan, Changhui; He, Yufeng; Li, Kai (Petroleum science and technology, 2021)
Accurate pore-size-distribution (PSD) is the key to comprehending porous media and shale rock characteristics. There are multiple methods for calculating the PSD of porous media. The Barrett-Joyner-Halenda (BJH) method is the most widely used and simplest calculation, and therefore, this study focus on the BJH algorithm to discuss the accurate shale PSD based on N 2 adsorption characteristics. Despite conducting more than a hundred experiments there are certain phenomena for which the calculated pore volume is smaller than the actual pore volume. Therefore, we combined the Brunauer-Emmet-Teller (BET) multilayer adsorption theory and Halsey adsorption equation to analyze the capillary evaporation and desorption demarcation points in the desorption isotherm of each shale sample, and a modified PSD calculation model was established. In addition, we applied the modified BJH algorithm to a homogeneous silicon material with the pore radius known, for calculating the theoretical pore radius and subsequently the pore radii; this allowed determining the correctness of the modified algorithm. The calculation error was approximately 5% that indicated the accuracy of this algorithm. Therefore, this study could provide meaningful insights into the accurate PSD calculation and gas-in-place estimation in shale nanoporous media.